A fluorescent probe based on aggregation-induced emission for hydrogen sulfide-specific assaying in food and biological systems. Issue 22 (8th October 2019) - Xu, Lingfeng; Ni, Ling; Sun, Lihe; Zeng, Fang; Wu, Shuizhu
Abstract : An AIE-based fluorescent probe was developed for monitoring food spoilage via its response toward hydrogen sulfide. Abstract : A fluorescent probe based on a triphenylamine benzopyridine platform for hydrogen sulfide (H2 S) assaying has been designed and synthesized. As a result of the H2 S-triggered cleavage reaction, the disappearance of the quenching effect of dinitrophenyl and the increased hydrophobicity in a poor solvent lead to the aggregation-induced emission (AIE) effect; consequently an obvious 'turn-on' fluorescence signal can be observed in this process. The probe TPANF features high selectivity towards H2 S, low detection limit (0.17 μM), and good photostability and biocompatibility. Moreover, it has been successfully utilized to monitor H2 S in food samples to distinguish the extent of food deterioration and to identify the H2 S concentration variation in living cells. In addition, endogenous H2 S in HCT-116 xenograft tumor tissues was imaged by using this probe. The approach could provide useful insight for the development of other activatable AIE-based probes that are potentially helpful for specific assaying in food chemistry and biological systems.